Առաքել վարդապետը և Դեղձուտի գրչության կենտրոնը - Մինասյան, Թամարա (Մատենադարան)
The article discusses the scriptorium of the Deghtzut monastery in the historical province Kayen. The personality of its head Aŗak‘el Vardapet is examined separately. According to the building inscription of 1274, Aŗak‘el arrived there from the Cilician province Tarsus and became the head of the monastery. However at that time a random person could not become head of a monastery. For this purpose, it was necessary to have at least received the vardapet degree from a distinguished prior of a monastery. It is also important that the vardapets of northern Armenia were overly scrupulous in confessional issues and someone coming from Cilicia would hardly have been entrusted with such a post if he had no proper local education. Our analysis of the facts leads to the conclusion that Aŗak‘el was a disciple of Vanakan Vardapet. Having received the archimandrite degree from him in the monastery of Khoranashat, he came to Deghtzut and founded a scriptorium there. В статье представлен скрипторий монастыря Дегцут исторической провинции Кайен. Особо рассматривается вопрос о личности настоятеля – вардапета (“учителя церкви”) Аракела. Согласно строительной надписи монастыря Дегцут (1274 г.), Аракел прибыл туда из киликийской провинции Тарс и стал его настоятелем. Случайный человек такой чин получить не мог. Для этого он должен был, по крайней мере, получить вардапетский посох от другого известного настоятеля. Важно и то обстоятельство, что вардапеты Северной Армении были чрезвычайно щепетильны в конфессиональных вопросах и приезжему из Киликии вряд ли доверили бы такой пост, если бы он не имел должного местного образования. Анализ фактов приводит к заключению, что Аракел был учеником Ваканана Вардапета; получив степень вардапета от Ванакана в монастыре Хоранашат, он прибыл в Дегцут и основал там скрипторий.
Keywords: Գրչություն